Mixed methods research: the five Ps framework - Cameron, Roslyn (Management Centre International, 2011)
Mixed methods research (MMR) is often referred to as the third methodological movement and has witnessed a rapid rise in popularity in the last 10 years. Prominent authorities in the field now refer to the MM research community which has developed its own philosophical, theoretical, methodological, analytical and practical foundations and constructs for the conduct of MMR. This paper provides a brief overview of some of the more common definitions of mixed methods research and methodology before introducing the conceptual framework of the Five Ps of mixed methods research. The Five P framework will be used to structure an exploration of some of the key challenges facing those who choose the innovative path of mixed methods research and some of the key areas for capacity building. The Five Ps include: Paradigms; Pragmatism; Praxis; Proficiency; and Publishing. This Five Ps framework will be mapped against the contemporary landscape of the MMR movement as developed by some of the most prominent mixed methodologists within the MMR community. These include: the overlapping components of an emerging map of MMR (Teddlie and Tashakkori 2010) and the domains of MMR (Creswell 2010). The Five Ps framework can provide those wishing to embark into mixed methods research with the essential components of a mixed methods starter kit, inclusive of a contemporary checklist of contentious issues, risks and traps that require consideration. Tashakkori and Teddlie (2010b: 29) refer to the need for MM researchers to become “methodological connoisseur[s]” whilst Cameron (2011: 263) calls for the need to build “methodological trilingualism” in those wishing to engage in MMR. Both these capacities require advanced research skill levels and competencies. As a consequence the framework also offers higher degree supervisors and educators with a pedagogic tool for guiding and teaching mixed methods.